2021
DOI: 10.1038/s41598-021-03265-0
|View full text |Cite
|
Sign up to set email alerts
|

Independent evaluation of 12 artificial intelligence solutions for the detection of tuberculosis

Abstract: There have been few independent evaluations of computer-aided detection (CAD) software for tuberculosis (TB) screening, despite the rapidly expanding array of available CAD solutions. We developed a test library of chest X-ray (CXR) images which was blindly re-read by two TB clinicians with different levels of experience and then processed by 12 CAD software solutions. Using Xpert MTB/RIF results as the reference standard, we compared the performance characteristics of each CAD software against both an Expert … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 44 publications
5
45
0
Order By: Relevance
“…Subgroup analyses showed that the performance of CADs can vary among some population demographic and clinical characteristics. All CAD systems performed worse in participants with a history of TB, something which has also been observed in previous studies [1315]. This is to be expected, as healed TB can leave residual CXR changes, which usually are classified as TB findings on CXR but can lead to negative microbiological test results.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Subgroup analyses showed that the performance of CADs can vary among some population demographic and clinical characteristics. All CAD systems performed worse in participants with a history of TB, something which has also been observed in previous studies [1315]. This is to be expected, as healed TB can leave residual CXR changes, which usually are classified as TB findings on CXR but can lead to negative microbiological test results.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, most studies used non-expert CXR interpreters and assessed an online CAD processing system or shared images with the CAD vendors and compared the performance against a suboptimal refence standard of a single sputum specimen tested with Xpert MTB/RIF which further highlights the need for independent and rigorous studies [8–12]. More recent investigations have focused on offline and multiple AI systems [1315], but they remain few in number.…”
Section: Introductionmentioning
confidence: 99%
“…48 An evaluation of 1032 images demonstrated that six out of 12 CAD platforms (Qure.ai, DeepTek, Delft Imaging, JF Healthcare, OXIPIT, Lunit) performed similarly to an expert reader, only three of which (Qure.ai, Delft Imaging and Lunit) performed significantly better than an intermediate reader. 49 A large evaluation of almost 24 000 outpatients, the majority of whom had symptoms, demonstrated that all five of the algorithms evaluated reduced the number of molecular tests required by 50% while maintaining an overall sensitivity of 90%. Two products: qXR (qure.ai, India) and CAD4TB (Delft Imaging Systems, Netherlands) met the triage TPP criteria.…”
Section: Overview Of Diagnostic Technologies and Tests By Specimen Typementioning
confidence: 99%
“…Thus these lessons learnt from several COVID-19 innovations in the health systems delivery during lockdowns, and the rapid development and rollout of diagnostics and vaccines highlight the need to stimulate ambitious political and scientific actions for revamping global TB control efforts whilst COVID-19 is brought under control (Ntoumi F et al, 2022a;2022b;Chakaya et al, 2022-IJID;Pai et al, 2022;Zimmer AJ et al, 2021;Ruhwald M et al, 2021Ruhwald M et al, , 2022Hopewell PC et al, 2020;Chapman H et al, 2021;Sahu S et al, 2021: Keene C et al, 2020. This should also include use of Artificial Intelligence (AI) for improved TB screening at all points of care and rapid data communication (Codlin et al, 2021: Malik et al, 2021. Obtaining accurate data on the actual global burden of LTBI, TB, DRTB, and TB-related deaths is essential to strengthen the evidence base required to convince media, governments and donors to pay specific attention to TB and its continuing status as a global public health emergency.…”
Section: Editorialmentioning
confidence: 99%